COVID-19 Vaccine Hesitancy and Early Adverse Events Reported in a Cohort of 7,881 Italian Physicians - Monami, M.; Gori, D.; Guaraldi, F.; Montalti, M.; Nreu, B.; Burioni, R.; Mannucci, E. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The COVID-19 vaccination campaign began in Italy at the end of December 2020, with the primary aim of immunizing healthcare professionals, using the EMA approved mRNA vaccines (Comirnaty® by Pfizer/BioNTech; mRNA-1273 by Moderna) and recombinant adenoviral vaccine (Vaxzevria® by AstraZeneca). The study aimed at evaluating the prevalence and motivations underlying Vaccine Hesitancy, as well as the incidence and type of adverse events associated with COVID-19 vaccination.Methods. Cross-sectional study. Data were collected January 1st to 28th 2021 using a purposely created online self-administered questionnaire from a selected cohort of Italian physicians.Results. Overall, 7,881 questionnaires were analyzed: 6,612 physicians had received one dose, and 1,670 two doses of Comirnaty®; 30 had received one dose of mRNA-1273. Vaccine Hesitancy rate was 3.6%; it correlated with prior SARS-CoV-2 infection, diabetes, Adverse Eventss at previous vaccinations and refusal of 2020 flu vaccine, and was mainly motivated by concerns about vaccine Adverse Events. Typical Adverse Events were pain/itching/paresthesia at the inoculation site, followed by headache, fever, fatigue and myalgia/arthralgia occurring more frequently after the second dose (77.8 vs 66.9%; p